Analytical issues in debt - Frenkel, Jacob A.; Dooley, Michael P.; Wickham, Peter (Washington, D.C.: International Monetary Fund, 1989)
This book presents a sample of the work of the IMF and that of world-renowned scholars on the analytical issues surrounding the explosion of countries with debt-servicing difficulties and describes debt initiatives and debt reduction techniques that hold the best promise for finding a lasting solution to the problems of debtor countries.
Includes bibliographical references (p. 412-415).
oif 12/07/16; usc 10/4/18
Loans
Keywords: Debts, External; Debt relief; Developing countries